Construction of chromosome segment substitution lines enables QTL mapping for flowering and morphological traits in Brassica rapa - Li, Xiaonan; Wang, Wenke; Wang, Zhe; Li, Kangning; Lim, Yong Pyo; Piao, Zhongyun (Frontiers in Plant Science, 2015)
Chromosome segment substitution lines (CSSLs) represent a powerful method for precise quantitative trait loci (QTL) detection of complex agronomical traits in plants. In this study, we used a marker-assisted backcrossing strategy to develop a population consisting of 63 CSSLs, derived from backcrossing of the F1 generated from a cross between two Brassica rapa subspecies: ‘Chiifu’ (ssp. pekinensis), the Brassica “A” genome-represented line used as the donor, and ‘49caixin’ (ssp. parachinensis), a non-heading cultivar used as the recipient. The 63 CSSLs covered 87.95% of the B. rapa genome. Among them, 39 lines carried a single segment; 15 lines, two segments; and nine lines, three or more segments of the donor parent chromosomes. To verify the potential advantage of these CSSL lines, we used them to locate QTL for six morphology-related traits. A total of 58 QTL were located on eight chromosomes for all six traits: 17 for flowering time, 14 each for bolting time and plant height, 6 for plant diameter, 2 for leaf width, and 5 for flowering stalk diameter. Co-localized QTL were mainly distributed on eight genomic regions in A01, A02, A05, A06, A08, A09, and A10, present in the corresponding CSSLs. Moreover, new chromosomal fragments that harbored QTL were identified using the findings of previous studies. The CSSL population constructed in our study paves the way for fine mapping and cloning of candidate genes involved in late bolting, flowering, and plant architecture-related traits in B. rapa. Furthermore, it has great potential for future marker-aided gene/QTL pyramiding of other interesting traits in B. rapa breeding.